2017
DOI: 10.3389/fimmu.2017.00594
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CD6-Mediated Interactions in the Regulation of Peripheral T-Cell Responses and Tolerance

Abstract: The CD6 lymphocyte receptor has been involved in the pathophysiology of different autoimmune disorders and is now considered a feasible target for their treatment. In vitro data show the relevance of CD6 in the stabilization of adhesive contacts between T-cell and antigen-presenting cells, and the modulation of T-cell receptor signals. However, the in vivo consequences of such a function are yet undisclosed due to the lack of suitable genetically modified animal models. Here, the in vitro and in vivo challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…However, contact-independent strong stimulation with anti-CD3/CD28 was not affected with addition of anti-CD6. Our observations are in line with a recent report that showed the absence of difference for in vitro Treg induction, between CD6 −/− and CD6 +/+ T cells, when under contact-independent and supra-physiological conventional conditions [39]. It was previously reported that Treg cells from CD6-deficient mice have reduced suppressive function [39].…”
Section: Discussionsupporting
confidence: 93%
“…However, contact-independent strong stimulation with anti-CD3/CD28 was not affected with addition of anti-CD6. Our observations are in line with a recent report that showed the absence of difference for in vitro Treg induction, between CD6 −/− and CD6 +/+ T cells, when under contact-independent and supra-physiological conventional conditions [39]. It was previously reported that Treg cells from CD6-deficient mice have reduced suppressive function [39].…”
Section: Discussionsupporting
confidence: 93%
“…2E-2H). T cell differentiation antigen CD6 and PTGES2 potentially conferring positive cell survival signals (72,73) were found up-regulated, whereas the down-regulation of TLR8 and FCGR1A may reduce immunogenicity (74,75). The mitochondrial stress management and DNA repair proteins (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…In case of the major B cell subset not constitutively expressing CD6 (B2), overactivation could result from other indirect causes such as a defective function of cells with regulatory/suppressive activity. Indeed, previous work from our group shows that steady state Cd6 −/− mice already present higher frequencies of regulatory T (Treg) cells with decreased suppressive activity ( Consuegra-Fernández et al., 2017 ; Orta-Mascaró et al., 2016 ). Ex vivo cell analyses showed that spleens from Cd6 −/− mice post-CLP-induced sepsis also undergo higher Treg cell induction, associated to lower induction of CD69 surface expression, a maker correlating with Treg suppressive function ( Yu et al., 2018 ) ( Figure S2 ).…”
Section: Discussionmentioning
confidence: 97%